Influence of Groove FM health arena programme on childhood immunisation: A study of residents of Owerri metropolis - Etumnu, Emeka Williams; Sylvie Marie, Eregbu; Chukwuemeka Njoku, Chidindu; Chinwe H., Nze; Williams Etumnu, Oluchi; Chike Martin, Nkwocha (COMMICAST, 2024)
This study examined the influence of groove fm health arena programme on childhood immunisation among residents of Owerri metropolis. The study was anchored on Yale persuasion theory. The researcher adopted survey research design for this study. The population consists of 555,500 Owerri metropolis residents and from this population a sample size of 384 was gotten using Wimmer and Dominick's online sample size calculator. The multi-stage sampling procedure was used in this study. Simple percentages were used to analyse the data after it was collected using a questionnaire. Finding revealed that 46.7% of the respondents indicated that Groove FM Health Arena programme has been able to influence them in carrying out childhood Immunisation to a large extent. The fact respondents are exposed to Groove FM Health Arena programme on childhood Immunisation to a large extent is commendable. Hence, the channel of communication should be leverage on by ministry of health or centre for disease control to communicate important messages as it concer health when the need arises. The producers of Health Arena programme should sustain their effort or even improve the content of the programme so as to continue enhancing audience knowledge on childhood Immunisation and other health issues. Residents should be encouraged to avail themselves to health programmes so as to be able to arm themselves with information that will help them in time of health issues or emergency.